Dampak Kebijakan Harga Pangan dan Kebijakan Moneter terhadap Stabilitas Ekonomi Makro - Ilham, Nyak; Siregar, Hermanto (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2007)
EnglishThe relatively high share of food expenses in household expenditure indicates that contribution of food prices to the inflation rate is still quite high. Inflation and its fluctuations are important variables affecting macroeconomic stability. Therefore, stabilizing food prices, which could lead to a more stable inflation, might potentially result in a more stable macroeconomy. Food price policy might play important role in stabilizing food prices; but could also disturb the stability if implemented improperly. This paper aims at analyzing effects of food price as well as monetary policies on macroeconomic indicators. For this analysis, quarterly data of the period 1980.1 to 2004.4 were utilized. The study used a Vector Error Correction Model (VECM), from which Impulse Response Function (IRF) analyzes were carried out. The results suggest that: (1) food price policy could not cause instability of macroeconomy, and (2) food price policy could not affect the unemployment rate, while monetary policy could do.IndonesianMasih besarnya pangsa pengeluaran pangan pada sebagian besar kelompok masyarakat berarti bobot inflasi kelompok pangan terhadap inflasi masih cukup besar. Inflasi dan fluktuasinya dapat mempengaruhi stabilitas ekonomi makro. Jadi stabilitas harga pangan dan harga-harga di tingkat makro secara potensial dapat dilakukan dengan menerapkan kebijakan harga pangan. Namun, kebijakan harga pangan yang tidak tepat dapat juga menyebabkan ketidakstabilan ekonomi makro. Tulisan ini bertujuan untuk menganalisis dampak kebijakan harga pangan dan kebijakan moneter terhadap keseimbangan dan stabilitas indikator-indikator ekonomi makro. Data yang digunakan merupakan data sekunder deret waktu triwulanan untuk periode 1980.1 - 2004.4. Analisis data menggunakan model VECM (Vector Error Correction Model) dan teknik IRF (Impulse Response Function). Hasil analisis menunjukkan bahwa kebijakan harga pangan tidak menyebabkan instabilitas ekonomi makro, sedangkan kebijakan moneter menyebabkan peningkatan angka pengangguran.